2007
DOI: 10.1007/bf03086013
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenic right ventricular cardiomyopathy: asymptomatic to life threatening as illustrated by the cases of two sisters

Abstract: Arrhythmogenic right ventricular cardiomyopathy: asymptomatic to life threatening as illustrated by the cases of two sisters Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a heart muscle disorder of unknown cause that is characterised by fibrofatty replacement, primarily of the right ventricular myocardium, which can lead to life-threatening arrhythmias. It is a disease with a very diverse phenotype. In the present article we describe two sisters, each with a different manifestation of this disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Furthermore, most patients harboring a mutation in ARVC-associated genes present with ARVC by 30 years of age although homozygous patients ( e.g ., Naxos disease) show 100% penetrance by adolescence 42 . Long-term cardiac monitoring by EKG, Holter monitoring, echocardiography, and exercise stress test is recommended for the patients harboring mutations in ARVC-associated genes as well as those presenting with PPK and hair shaft anomalies with unknown genotype; however, it was reported that only 2.3% of patients with such cutaneous phenotypes receive relevant cardiac monitoring 41 , 42 . In this context, because of age-dependent penetrance and the young age of our patients, further studies and close follow-up are needed, including cardiological monitoring of family members at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most patients harboring a mutation in ARVC-associated genes present with ARVC by 30 years of age although homozygous patients ( e.g ., Naxos disease) show 100% penetrance by adolescence 42 . Long-term cardiac monitoring by EKG, Holter monitoring, echocardiography, and exercise stress test is recommended for the patients harboring mutations in ARVC-associated genes as well as those presenting with PPK and hair shaft anomalies with unknown genotype; however, it was reported that only 2.3% of patients with such cutaneous phenotypes receive relevant cardiac monitoring 41 , 42 . In this context, because of age-dependent penetrance and the young age of our patients, further studies and close follow-up are needed, including cardiological monitoring of family members at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al 2011Garcia-Gras et al 2006  Munkholm et al 2012Asimaki et al 2007   Huang et al 2008  Plakophilin-2Gerull et al 2004Otterspoor et al 2007  Antoniades et al 2006Aneq et al 2011Awad et al 2006bAdachi and Isobe 2011Calkins 2006Gandjbakhch et al 2011Dalal et al 2006Gehmlich et al 2011aKannankeril et al 2006Kapplinger et al 2011Nagaoka et al 2006Larsen et al 2011Syrris et al 2006aNakajima et al 2011van Tintelen et al 2006Ostrowska Dahlgren et al 2011 Pamuru et al 2011Joshi-Mukherjee et al 2008Paul et al 2011Lahtinen et al 2008van der Zwaag et al 2011aRam and Van Wagoner 2008Zhang et al 2012Tandri et al 2008  Bhuiyan et al 2009den Haan et al 2009Fidler et al 2009Hall et al 2009Qiu et al 2009Watkins et al 2009Wu et al 2009  Christensen et al 2010aChristensen et al 2010b…”
mentioning
confidence: 99%